Analisis Kualitas Pelayanan Rawat Inap Pada Puskesmas Winongan Kabupaten Pasuruan - Budiono; Ahmad Robbah (Sawala : Jurnal Administrasi Negara, 2021)
The study was compiled to see and analyze the quality of care services at Winongan Public Health Center, Pasuruan Regency, and to see the factors that affect inpatient services. This research is a qualitative descriptive study by observing data through interviews, documentation, and observation. The informants taken by the researcher were the Head of the Inpatient Division of the Winongan Public Health Center, Pasuruan Regency, Administrative Officers, Nurses and patients and / or their families. In this study, the researcher used 5 public service indicators, namely Tangible, Reliability, Responsiveness, Assurance, and Empathy. The results showed that the total quality of services at Winongan Health Center has been carried out well. This means that the quality of the services provided by the Winongan Health Center is maximized. This can be seen from the results of interviews and data that have been previously described that the Tangible, Reliability, Responsiveness, Assurance, and Empathy indicators. then the implementation of Inpatient services at Winongan Health Center is running well, but still requires improvement in several ways, namely: lack of supplies of medical equipment, linen and household tools, cleanliness of rooms and bathrooms, implementation of actions according to Standard Operating Procedures (SOP) and motto that has been set.